Hubungan antara Academic Self Efficacy dengan Motivasi Belajar Mahasiswa Fakultas Psikologi Universitas Negeri Makassar - Damayanti, Sintia Dwi; Alwi, M. Ahkam (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to determine the relationship between Academic Self Efficacy and Learning Motivation of Students at the Faculty of Psychology, Makassar State University. The research method uses quantitative methods. The population in this study were all students of the Faculty of Psychology, Makassar State University in 2023 with a sampling technique using the accidental sampling method. The results of research involving 358 students from the Faculty of Psychology, Makassar State University, show that there is a relationship between Academic Self Efficacy and Learning Motivation of Students from the Faculty of Psychology, Makassar State University. It is hoped that the implications of this research can be a consideration for future researchers to pay more attention to other factors that can be related to learning motivation.